Sosialisasi bahaya cybercrime di era digitalisasi di Sekolah Menengah Atas di Kabupaten Sampang - Khirdany, Elvin Nury; Aini, Laily Nur; Rokip, Rokip; Nurhidayah, Alifah (Tintamas: Jurnal Pengabdian Indonesia Emas, 2025)
The rapid development of this technology not only provides benefits for its users and gives rise to crime cases (cybercrime). Many cases of crime occur in cyberspace, which is currently busy. It is important to understand internet security to identify possible threats and learn how to overcome them. This activity was carried out at SMA Darussyahid Sampang to give students a sense of awareness of the dangers of crime in cyberspace. The methods used in this community service are surveys, lectures, and discussions. It is hoped that this socialization will open up teenage students to understand how to secure personal data on virtual media. This community service provides benefits both for service partners or participants and for service members, including increasing knowledge regarding the dangers of cybercrime in cyberspace so that students are more careful when using social media, keeping the data safer from the dangers of cybercrime; after participating in the training, participants expressed a high level of satisfaction with the implementation.